Análise de morfologia de fundo na região do Rio Pará através da sísmica da reflexão - PINTO, Nara de Sena Souza (2019)
The estuary of the Para River hydrographic comprises a set formed by numerous rivers whose waters flow into it, giving rise to a succession of bays and coves that stretch along the entire southern coast of Marajo, located in the central portion - the West “Golfão Marajoara” is of fundamental importance for understanding the regional geomorphology. Based on these characteristics, the main objective of this study was the analysis and interpretation of the bottom morphology through high resolution seismic Para River region and the comparison with the nautical chart of DHN. The development work is on: the bibliographic characteristics of the study area and the seismic reflection high resolution; survey of seismic profiles, which are two longitudinal (L1 and L2-L1-L2 ') and three transverse (PP ', T1, T1' and T2-T2 '); digital processing of seismic profiles, and digital processing of bathymetric profiles, obtained from nautical charts (304 and 305) obtained by the site of DHN Navy. This allowed for the morphological analysis and interpretation of background, by comparing the bathymetric and seismic data. The seismic profiles were made from the software Discovey SB Surfer 9 and Photoshop CS5, and for the preparation of bathymetric profiles using the software Arc GIS 9.3. and Global Mapper 11. The transverse profiles (PP ', T1-T1' and T2-T2 ') in general morphology as the main results presented background as a system of channels and banks, the longitudinal profiles (L1-L1'and L2-L2 ') channels showed relief plan and banks with overlapping sandwaves. In all seismic profiles morphologies background were compared to data from bathymetric charts, it was observed that the seismic profiles allow better identification of morphologies background due to its higher resolution, beyond the possibility of obtaining smaller features such as sandwaves, can also achieve better results in diferentestipos sediment, so different from bathymetric profiles that allow for the identification of bottom morphology but lower resolution. These results are due to difference frequency sources used by each acquisition (seismic and bathymetric). Drawing on the importance of the results obtained with sources of higher resolution, as this study shows the Navy is already implementing equipment for multibeam data acquisition more precisos.Além the seismic profiles offer the advantage of better resolution of morphologies background, compared the bathymetric profiles, also allow the identification of the thickness of sedimentary layers and basement rock. However, this work could not this type of identification due to poor penetration of acoustic waves.